Low-temperature heat capacity of fullerite C₆₀ doped with nitrogen - Gurevich, A.M.; Terekhov, A.V.; Kondrashev, D.S.; Dolbin, A.V.; Cassidy, D.; Gadd, G.E.; Moricca, S.; Sundqvist, B. (Физика низких температур, 2006)
The heat capacity Cm of polycrystalline fullerite C₆₀ doped with nitrogen has been measured in
the temperature interval 2–13 K. The contributions to the heat capacity from translational lattice
vibrations (Debye contribution), orientational vibrations of the C₆₀ molecules (Einstein contribution),
and from the motion of the N₂ molecules in the octahedral cavities of the C₆₀ lattice have
been estimated. However, we could not find (beyond the experimental error limits) any indications
of the first-order phase transformation that had been detected earlier in the dilatometric investigation
of the orientational N₂–C₆₀ glass. A possible explanation of this fact is proposed.